# How do you solve 3(x + 1) = -2(x - 1) - 4?

Apr 23, 2016

$3 \left(x + 1\right) = 2 \left(- x + 1\right) - 4$
$3 x + 3 = - 2 x + 2 - 4$
$3 x + 3 = - 2 x - 2$
$5 x = - 5$
$x = - 1$

#### Explanation:

First you need to expand out the brackets on both sides of the equals sign.

$3 \left(x + 1\right)$
$3 x + 3$

Times the $3$ on the outside of the first set of brackets by $x$ and then by $1$. This makes $3 x + 3.$

Now expand the second set of brackets out. Remember that the $- 4$ has nothing to do with this set of brackets.

$2 \left(- x + 1\right)$
$- 2 x + 2$

Here, you times $2$ by $- x$. This makes $- 2 x$. Then you times $2$ by $+ 1$. This makes $+ 2$.

Now write out the sum with the newly expanded brackets and the $- 4$.

$3 x + 3 = - 2 x + 2 - 4$

Collect the like terms on each side of the equals sign to make:

$3 x + 3 = - 2 x - 2$

I did the sum $+ 2 - 4$ to work this out.

Now you have to collect all the $x$'s on one side and the other numbers on the other side.

$3 x + 3 = - 2 x - 2$

To cancel out $- 2 x$ you must $+ 2 x$ on each side of the equals sign.

$5 x + 3 = - 2$

Then, to get rid of the $+ 3$ on the left side of the equals sign, you must $- 3$ from each side of the equals sign.

$5 x = - 5$

Finally, to cancel down the answer, divide both sides of the equals sign by $5$ because both sides are divisible by $5$.

$x = - 1$